FRI0622 Trends in encounters with rheumatologists in a publicly-funded single payer healthcare system. (12th June 2018) - Widdifield, J.; Bernatsky, S.; Ahluwalia, V.; Barber, C.; Eder, L.; Kuriya, B.; Ling, V.; Lyddiatt, A.; Paterson, M.; Pope, J.; Thorne, C.
Abstract : Background: Rheumatology workforces are challenged by too few physicians, increasing incidence and prevalence of MSK diseases (and complexity of co-morbid conditions) in aging populations, and expanding therapeutic options that increase demand for service. Understanding trends in rates of rheumatology encounters with new and existing patients will help to identify why patients have delays to rheumatology care and mobilize efforts to help meet patients' needs. Objectives: To describe trends in patient encounters with rheumatologists over time in Ontario, Canada. Methods: We analyzed administrative health data from 2000 to 2013 in Ontario, Canada, where all 13 million residents are covered by a publicly-funded healthcare system and access to rheumatologists is dependent upon referrals. During this time, Ontario had a stable rheumatology supply of 1 rheumatologist per 75, 000 population (0.7 FTEs/75, 000). We determined annual incident, follow-up and total patient encounters seen by rheumatologists. Rates were calculated using the total population of Ontario residents 18 and older, each year. Diagnosis codes assigned at each encounter were used to assess changes in the case-mix of patients under rheumatology care over time. Results: From 2000 to 2013, the proportion of all Ontario residents seen by rheumatologists was constant over time (2.7%). The total number of rheumatology encounters increased from 561, 452 to 742, 952 but the total encounter rate remained relatively stable over time (table 1). The annual new consultation rate significantly declined over time from 1.6 to 0.8 new patients per 100 population. Both the annual proportion of incident patients and the ratios of incident to established patients and incident to total patient encounters declined significantly over time. We observed a shift in the diagnostic case-mix over time: encounter rates for systemic inflammatory conditions significantly increased over time and encounter rates for non-systemic conditions (OA, regional MSK conditions) decreased. The volume of rheumatoid arthritis (RA) encounters increased the most, with 17% of all rheumatology encounters related to RA in 2000 versus 32% in 2013. Conclusions: The significant decline in new patient consultation rates over time helps illustrate the growing supply-demand mismatch in rheumatology care. An increasing fraction of rheumatology encounters in Ontario are with established patients, which may be limiting access for new consultations and increasing wait times. We also observed a shift in the patient case-mix over time with rheumatologists seeing/prioritizing more systemic inflammatory conditions. Our findings provide new inputs for rheumatology workforce planning models. Disclosure of Interest: None declared